2017 IEEE 30th International Symposium on Computer-Based Medical Systems (CBMS) 2017
DOI: 10.1109/cbms.2017.164
|View full text |Cite
|
Sign up to set email alerts
|

PhytoCloud: A Gamified Mobile Web Application to Modulate Diet and Physical Activity of Women with Breast Cancer

Abstract: In case of abuse or copyright appearing without permission e-mail repository@westminster.ac.uk PhytoCloud: A gamified Mobile Web Application to modulate diet and physical activity of women with breast cancer Abstract-Breast cancer incidence and mortality rates vary geographically reflecting factors including regional and cultural differences in diet and lifestyle. There are numerous successful commercial mobile apps to help people control their diet and manage weight. However, such products are not suitable fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The solution presented here attempts to address the particular needs and requirements of breast cancer survivors for PA apps by taking a UCD approach for the conceptualization of the tool. Few are the systems in the literature designed with such a purpose, with only 4 apps identified that had some component of PA coaching for these individuals [ 23 , 24 , 28 , 29 ]. Compared with such apps, our solution targets aerobic exercise, specifically walking, which has been suggested as the preferred activity for these individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The solution presented here attempts to address the particular needs and requirements of breast cancer survivors for PA apps by taking a UCD approach for the conceptualization of the tool. Few are the systems in the literature designed with such a purpose, with only 4 apps identified that had some component of PA coaching for these individuals [ 23 , 24 , 28 , 29 ]. Compared with such apps, our solution targets aerobic exercise, specifically walking, which has been suggested as the preferred activity for these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, a few PA apps reported in the literature target breast cancer survivors [ 11 , 24 , 28 , 29 ]; however, these seemed to be in the early stages of development and evaluation and lack proper reporting of design decisions. Only the papers describing the Bounce app presented clear details on the design process, behavioral theory foundations, and features [ 24 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The remaining 10 papers were scrutinized for eligibility, and all of them met the inclusion criteria. 21,[44][45][46][47][48][49][50][51] A questionnaire was constructed to determine the information content and functions of the mobile-based self-care application for patients with BCRL based on literature review. The questionnaire was composed of four main parts, including (1) the participants' demographic characteristics (i.e., age, marital status, and education for patients and age, gender, work experience, work experience in lymphedema clinic, and specialist field for experts), (2) 14 and 21 administrative and clinical information, (3) 19 items about lifestyle educational needs, and (4) 35 items concerning the functions (i.e., drug use, nutrition, communication, exercise, smoking cessation, and test time reminder) for participants (patients and experts).…”
Section: Methodsmentioning
confidence: 99%
“…PhytoCloud is a mobile web application that focuses on breast cancer patients and which enables users to record their dietary habits and physical activity and motivates them to consume food with estrogen-like properties. This allows them to control their own goals and motivates them to achieve them and adopt healthier eating habits, while also increasing physical activity, in order to ensure an improvement in their lifestyle and wellbeing [9].…”
Section: Related Workmentioning
confidence: 99%